Handbook of research on electronic collaboration and organizational synergy [ - Salmons, Janet , 1952-; Wilson, Lynn , 1954- (Information Science Reference, 2009)
"This book presents a collection of empirical work that examines techniques, strategies and effects of electronic collaboration across disciplines and sectors"--Provided by publisher